A survey on the use of continuous positive airway pressure in newborn care in Kenya in 2017–2018 - Jemma L. Wright; Emma Haddon; Helen M. Nabwera; Fiona M. Dickinson; Mary-Jo Hoare; Pamela Godia; Judith Maua; Mercy K. Sammy; Bridget C. Naimoi; Onesmus Muchemi; Sylvia Kawira; Joyce Mutuku; et al. (PLoS ONE, 2025)
Background Globally, complications of preterm birth are the leading cause of under-5-mortality. Respiratory distress syndrome (RDS) is a common and life-threatening complication among preterm infants. Continuous positive airway pressure (CPAP) is a relatively simple and effective intervention that is recommended for RDS treatment. However, appropriate infrastructure and processes are required to ensure that it is used safely, effectively and sustainably. This study describes how CPAP was used in newborn care in Kenya between 2017–2018. Our aim was to identify enablers, barriers and gaps in CPAP use. Methods A cross-sectional survey was carried out across all newborn baby units in Kenya between 2017–2018, as part of a evaluation of CPAP use in newborn care. Descriptive statistics were used to analyse the quantitative data. Results Twenty-three hospitals across 15 (32%) of the counties in Kenya were providing CPAP in newborn care. The survey was conducted in 19 hospitals, amounting to 83% of all hospitals providing CPAP in newborn care in the country. Sub-county (level 4) and county (level 5) referral had fewer resources (i.e., trained staff, infrastructure and equipment) than the national referral (level 6) and private hospitals. In addition, there was a wide variation in the CPAP devices used and the resources for supporting CPAP use across different hospitals. Conclusion We found access to CPAP for neonates with RDS was inequitable in Kenya. There were also disparities in the availability of resources, personnel, and guidelines to support its implementation. Lack of standardisation of CPAP use in newborn care was especially evident in the public sector. To optimise coverage and standardisation of CPAP use in newborn care in Kenya, our results support ongoing partnerships to strengthen public and private healthcare sectors involving the implementation of strategies to improve infrastructure for newborn care, train and retain staff, and provide additional equipment.